Proprioceptive neuromuscular facilitation training induced alterations in muscle fibre type and cross sectional area - Kofotolis, N.; Vrabas, I. S.; Vamvakoudis, E.; Papanikolaou, A.; Mandroukas, K. (British Journal of Sports Medicine, 2005)
Objectives: To compare the effects of proprioceptive neuromuscular facilitation (PNF) and isokinetic training on fibre type distribution and cross sectional area of the vastus lateralis muscle.